2008
DOI: 10.1074/jbc.m708662200
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Calcitonin Gene-related Peptide Enhancer by Upstream Stimulatory Factor in Trigeminal Ganglion Neurons

Abstract: The neuropeptide calcitonin gene-related peptide (CGRP) is a key player in migraine. However, the transcription factors controlling CGRP expression in the migraine-relevant trigeminal ganglion neurons are unknown. Previous in vitro studies demonstrated that upstream stimulatory factor (USF) 1 and USF2 bind to the CGRP neuroendocrine-specific 18-bp enhancer, yet discrepant overexpression results in cell lines, and the ubiquitous nature of the USF cast doubts about its role. To test the functional role of USF, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
(83 reference statements)
0
16
0
1
Order By: Relevance
“…Rat2 cell line (ATCC, Manassas, VA, USA) was maintained in Dulbecco’s Modified Eagle’s Medium (high glucose), 10% fetal bovine serum, penicillin (100 units/ml) and streptomycin (100 μg/ml) at 37°C in 5% CO 2 . Rat trigeminal ganglia cells were isolated and dispersed as described (17). Rat trigeminal glial cultures were prepared as described (14), with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rat2 cell line (ATCC, Manassas, VA, USA) was maintained in Dulbecco’s Modified Eagle’s Medium (high glucose), 10% fetal bovine serum, penicillin (100 units/ml) and streptomycin (100 μg/ml) at 37°C in 5% CO 2 . Rat trigeminal ganglia cells were isolated and dispersed as described (17). Rat trigeminal glial cultures were prepared as described (14), with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Primers were: CT/CGRP (GenBank M11597.1) exon 2 sense 5′-CCCTTTCCTGGTTGTCAGCATCTT-3′, exon 3 antisense 5′-CATGCCTGGGCTGC TTTCTAAGGTT-3′, CT (GenBank V01228.1) exon 4 antisense 5′-AGCATGCAGGTACTCAGATTCCCA-3′. CGRP (GenBank M11597) exon 3 sense and exon 5 antisense have been described (17). For NCI-H460 cells: 730 ng of RNA was reversed transcribed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much has been discovered about the regulation of the Calca gene in recent years. Transcription factors USF1 and USF2 are activators of the gene 23 , but their ubiquitous expression pattern led to questions about how tissue specificity is maintained. We previously reported that the gene was kept silent in glia through an epigenetic mechanism 24 .…”
Section: Introductionmentioning
confidence: 99%